2017
DOI: 10.18196/ijnp.1257
|View full text |Cite
|
Sign up to set email alerts
|

Remaja Bisa Mencegah Gizi Lebih Dengan Meningkatkan Self-Efficacy Dan Konsumsi Sayur-Buah

Abstract: Prevalensi gizi lebih pada remaja setiap tahunnya mengalami peningkatan. Gizi lebih merupakan suatu masalah yang kompleks yang dipengaruhi oleh banyak faktor, salah satunya kurangnya konsumsi sayuran dan buah. kurangnya konsumsi sayuran dan buah di asumsikan tidak adanya keyakinan (self-efficacy) pada remaja untuk mengonsumsi sayuran dan buah karena beberapa hal. Tujuan dari penelitian ini adalah untuk mengetahui hubungan self-efficacy dengan konsumsi sayuran-buah dan kejadian gizi lebih. Metode yang digunakan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Adolescents who consumed enough fruits and vegetables had logodds for obesity 1.16 units lower than those who ate less fruits and vegetables (b = -1.16; 95% CI = -1.88 to -0.44; p = 0.002). In line with the study of Widianto et al (2017) about adolescent nutrition obtained an analysis of the relationship between efficacy and consumption of vegetables and fruits obtained that as many as 71 (93.4%) adolescents with efficacy that lacked the amount of consumption of vegetables and fruits is less. Adolescents in the category of efficacy are good, with 32 (40%) good consumption of vegetables.…”
Section: The Effect Of Fruit and Vegetable Consumption On The Risk Of Obesity In Adolescentsmentioning
confidence: 60%
“…Adolescents who consumed enough fruits and vegetables had logodds for obesity 1.16 units lower than those who ate less fruits and vegetables (b = -1.16; 95% CI = -1.88 to -0.44; p = 0.002). In line with the study of Widianto et al (2017) about adolescent nutrition obtained an analysis of the relationship between efficacy and consumption of vegetables and fruits obtained that as many as 71 (93.4%) adolescents with efficacy that lacked the amount of consumption of vegetables and fruits is less. Adolescents in the category of efficacy are good, with 32 (40%) good consumption of vegetables.…”
Section: The Effect Of Fruit and Vegetable Consumption On The Risk Of Obesity In Adolescentsmentioning
confidence: 60%
“…Self-efficacy provides the achievement of goals because it is the first step of planning and performing behavior of individuals15. Poor consumption of vegetables and fruits means that there is no self-efficacy for adolescents to consume vegetables and fruits for certain reasons (Widianto, 2017) Self-efficacy is measured using questionnaire containing 6 statements. Based on the statement analysis, it is found that 90% of the subjects said that fruits and vegetables consumption is not a big deal.…”
Section: Discussionmentioning
confidence: 99%
“…Informasi dan motivasi secara langsung mempengaruhi efikasi diri salah satunya yaitu memprediksi perilaku yang mempromosikan kesehatan. 28 Berdasarkan salah satu penelitian 30 mengatakan bahwa tingkatan self-efficacy menjelaskan bahwa terkait perubahan atau mengubah perilaku seseorang untuk pertama kali harus ada niat untuk melakukan perubahan dan niat tersebut dapat terbentuk dari self-efficacy yang sudah direncanakan sebelum melakukan atau menerapkan kegiatan agar target dapat tercapai. Berdasarkan penelitian yang dilakukan pada remaja putri SMP terkait evaluasi pengaruh edukasi gizi menggunakan Health Believe Model menyatakan bahwa edukasi gizi secara positif meningkatkan pengetahuan, sikap dan perilaku.…”
Section: Pembahasanunclassified